2013
DOI: 10.12938/bmfh.32.107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Salivary IgA Secretion Rate Collected by the Aspiration Method and Swab Method

Abstract: Salivary immunoglobulin A (IgA) is used as an immunity marker, as saliva can be easily collected, noninvasively with little stress. However, several saliva collection methods can be used. Our comparison between samples collected using different methods demonstrated that the salivary IgA secretion rate in samples collected using an aspiration method was significantly correlated with that in samples collected using a swab method. Moreover, the significant circadian variation in salivary IgA secretion rate in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
6
0
3
Order By: Relevance
“…Although we need at least 2.5 μL saliva for the IgA assay, a combination of PBS and NE injection did not yield enough volume of saliva. It has been reported that the aspiration method does not suppress the diurnal variation in salivary IgA secretion compared to the swab method in human experiments 32 . Therefore, we used pipettes to collect saliva.…”
Section: Methodsmentioning
confidence: 94%
“…Although we need at least 2.5 μL saliva for the IgA assay, a combination of PBS and NE injection did not yield enough volume of saliva. It has been reported that the aspiration method does not suppress the diurnal variation in salivary IgA secretion compared to the swab method in human experiments 32 . Therefore, we used pipettes to collect saliva.…”
Section: Methodsmentioning
confidence: 94%
“…Secretory immunoglobulin A (S-IgA) is the most abundant immunoglobulin in saliva, and plays a critical role in mucosal immunity [ 20 ]. S-IgA concentrations were used as a noninvasive indicator of immunity [ 21 ] and/or environmental stress [ 22 ]. Several studies reported that salivary S-IgA concentrations also exhibited diurnal variations.…”
Section: Introductionmentioning
confidence: 99%
“…Technically, the circadian rhythms of immunoglobulin A production in the saliva is important. Regarding sampling, aspiration turned out to be superior to swabs 126 . Furthermore, also the detection of different bacteria such as Firmicutes including Streptococcus and Gemella, and Bacteroidetes including Prevotella 127 is subject to variation.…”
Section: Microbiome In Otorhinolaryngologymentioning
confidence: 88%
“…Technisch ist die zirkadiane Rhythmik u. a. der Immunglobulin-A-Produktion im Speichel von Bedeutung. Hier zeigte sich das Aspirat der Probengewinnung mittels Abstrich überlegen 126 . Weiterhin unterliegen auch der Nachweis von verschiedenen Bakterien, wie Firmicutes inkl.…”
Section: 41 Mikrobiom Des Speichelsunclassified